Ming tea murder [large type] - Childs, Laura (Childs, Laura. Tea shop mystery, 2015)
Normally Theodosia Browning wouldn't attend a black tie affair for all the tea in China. But she can hardly say no to her hunky boyfriend Max, who has organized a gala opening for an exhibit of a genuine 18th-century Chinese teahouse and invited the crème de la crème of Charleston society. In the Gibbers Museum's rotunda, a Chinese dragon dances to the beat do drums in an exotic garden -- as Theodosia discovers the body of museum donor Edgar Webster.